Remote Working Adoption Strategies and Employee Performance during COVID-19 Pandemic: A Case Study of MTN Uganda Limited - Begumisa, Innocent; Kamaduuka, Regis Zombeire; Mubiru, Pontious; Kizza, James (East African Journal of Business and Economics, 2023)
This study examined the effect of remote working adoption strategies on employee performance at MTN (U) Ltd during the COVID-19 pandemic. Specifically, the study analyses the effect of flexible work schedules, technology accessibility and remote worker motivation on employee performance in remote working at MTN Uganda. The study adopted a descriptive research design, employing quantitative and qualitative research approaches. Quantitative data was collected from a sample of 89 respondents using questionnaires, and qualitative data was collected from 5 key informants using interviews. Data was analysed using Pearson's correlation and regression analysis with the help of Statistical Packages for Social Scientists (SPSS version 25). The study finds a significant positive relationship between flexible working schedules and employee performance (r = 0.594, p = 0.000); technology accessibility and employee performance (r =0.616, p = 0.000); and remote worker motivation and employee performance (r=0.273, p=0.010). The explanatory variables jointly explain 57.3% of the variations in employee performance in remote working at MTN (U) (R-squared = 0.573; p<0.000). It is recommended that MTN (U) Ltd and other telecom companies improve the flexibility of their work as one way to enable employees to adopt remote working during periods of crisis such as pandemics and epidemics. This is to enable continuous workflow. There is a need to invest in technology and make it accessible to all employees, and create motivation packages such as fringe benefits that seek to motivate employees working remotely to enable them to embrace remote working and improve their performance